2005
DOI: 10.1093/bja/aei228
|View full text |Cite
|
Sign up to set email alerts
|

Late preconditioning with isoflurane in cultured rat cortical neurones

Abstract: Isoflurane induced late preconditioning in cultured rat cortical neurones. Ischaemic and pharmacological preconditioning with diazoxide and isoflurane induced ischaemic tolerance in the cultured neurones via mitoK(ATP) channels without an increase in Kir6.2 expression, and induced upregulation of EAAC1 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 23 publications
(23 reference statements)
1
23
0
Order By: Relevance
“…In recent years, several studies showed that preconditioning by anesthetics exerted neuroprotective effects against cerebral ischemia in vitro and in vivo (Kawaguchi et al 2004, Kaneko et al 2005. As one of the important inhalational anesthetics, sevoflurane has been investigated in various models using both immediate and delayed preconditioning paradigms .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, several studies showed that preconditioning by anesthetics exerted neuroprotective effects against cerebral ischemia in vitro and in vivo (Kawaguchi et al 2004, Kaneko et al 2005. As one of the important inhalational anesthetics, sevoflurane has been investigated in various models using both immediate and delayed preconditioning paradigms .…”
Section: Discussionmentioning
confidence: 99%
“…For example, the protective preconditioning effect of volatile anesthetics has been demonstrated in neurons 1115 , cardiac cells 32, 33 , epithelial cells 34 , and kidney cells 35 . Until now, however, no reports had considered innate cell sex in the response to anesthetics despite the sex differences reported in isoflurane preconditioning in vivo 1, 4, 5 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most reports investigating anesthetic preconditioning at the cellular level in the brain have been limited to mixed-sex primary neuronal cultures 1115 , leaving the role of astrocytes unexplored. Astrocytes comprise the majority of brain cells in mammals and are crucial in central nervous system function 16, 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Rapid and delayed preconditioning in both the heart and brain acts via different mechanisms. Generally, early preconditioning is related to a rapid response such as changes in ion channel permeability and post-translational modifications of proteins, while late preconditioning involves gene activation and protein synthesis [172,173,174,175]. …”
Section: Ncrnas In Brain Development and Ischemic Injurymentioning
confidence: 99%